Perdón, restitución y teatro musical: Antonio de Zamora y su visión poético-musical de los sublevados españoles durante la Guerra de Sucesión. - BERMEJO GREGORIO, JORDI (Scripta, 2018)
This work studies the speech of Antonio de Zamora about the remorse and restitution of the loyalty towards Philip V directed to the Spanish rebels during the War of Succession. It will prove that the propagandistic and rhetorical importance that the poetic-musical and spectacularly forms of palatial dramas acquired to send out that political message --especially in the case of zarzuela Viento es la dicha de amor (1708).